2012
DOI: 10.4274/jcrpe.856
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function and Obesity

Abstract: Nowadays, childhood obesity is one of the biggest health emergencies in the developed countries. Obesity leads to multiple metabolic alterations which increase the risk of developing diabetes and cardiovascular diseases. Thyroid function has been often described as altered in obese children, however, it is not clear whether the altered thyroid function is the cause or the consequence of fat excess. On the other hand, thyroid structure seems also to be affected. Nevertheless, both functional and structural alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 46 publications
0
21
0
3
Order By: Relevance
“…Increase in leptin levels and cytokines secreted from adipose tissue causes increase in deiodinase activity and decrease in iodine uptake in thyroid tissue. Changes in thyroid function are reversible and thyroid function tests become normal after losing weight ( 42 ). Thyroid hormone is an important modulator in the lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in leptin levels and cytokines secreted from adipose tissue causes increase in deiodinase activity and decrease in iodine uptake in thyroid tissue. Changes in thyroid function are reversible and thyroid function tests become normal after losing weight ( 42 ). Thyroid hormone is an important modulator in the lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, plasma exudation and imbibition of parenchyma occur. This situation differs from the autoimmune thyroiditis that was confirmed by a fine-needle biopsy, which did not show lymphocyte infiltrations, ruling out Hashimoto's disease as a cause of parenchyma derangement [21]. It is also suggested that the hypoechogenic image of the thyroid gland in obese subjects may result from the accumulation of adipose tissue [15].…”
Section: Does Obesity Influence Ultrasound Imaging Of the Thyroid Gland?mentioning
confidence: 78%
“…In summary, in adult obese individuals the prevalence of thyroid autoimmunity (assessed by the presence of antithyroid antibodies) does not differ from the normal-weight population even in those with elevated TSH levels. In contrast, in a study performed in paediatric obese patients, antithyroid autoantibodies were found significantly more often than in normal-weight peers [21]. The prevalence of elevated aTPO and aTG levels in obese subjects in different populations is summarised in Table II.…”
Section: Does Obesity Increase the Risk Of Aitd?mentioning
confidence: 86%
“…As mentioned previously, high levels of leptin have been found in adults and children with obesity. Likewise, the development of secondary hypothyroidism has been reported in subjects with leptin deficiency or resistance [18,61]. Leptin also regulates central and peripheral Ds activity, affecting deiodination (and therefore the bioactivity) of T4 and T3 [62].…”
Section: Prace Poglądowementioning
confidence: 97%
“…It is generally accepted that a positive energy balance (obese subjects) presents increased TSH and free T3 concentrations [18]. On the other hand, a negative energy balance in obese and thin humans inhibits the activity of the HPT, and gonadal and hypothalamuspituitary-somatotrope axis, while stimulating the adrenal axis [19].…”
Section: Prace Poglądowementioning
confidence: 99%